Diagnostic accuracy of acoustic radiation force impulse elastography (ARFI) in comparison to other non-invasive modalities in staging of liver fibrosis in chronic HCV patients: single-center experience. - Alem, Shereen Abdel; Abdellatif, Zeinab; Mabrouk, Mahasen; Zayed, Naglaa; Elsharkawy, Aisha; Khairy, Marwa; Musa, Sherief; Anwar, Ismail; Yosry, Ayman (Abdominal Radiology, 2019)
Purpose: To evaluate the reliability of ARFI elastography for liver fibrosis staging and compare it to other non-invasive assessment of hepatic fibrosis (FIB-4 and APRI) in chronic HCV (CHC) patients. Methods: A single-center, prospective study included 2103 CHC patients. Liver stiffness (LS) was evaluated by TE and ARFI elastography. FIB-4 and APRI were calculated. The area under the receiver-operating characteristic curve (AUROCs) was used to assess the diagnostic performance of ARFI elastography for staging of liver fibrosis using TE as a reference standard. Results: The best cut off values of ARFI elastography for diagnosis of ≥ F2, ≥ F3and F4 were 1.36 m/s, 1.45 m/s, and 1.7 m/s with AUROCs of 0.89, 0.94 and 0.95, respectively. ARFI elastography cut offs are lower in patients with normal ALT level compared to those with ALT level (1.1–< 3 ULN) and those with ALT level ≥ 3ULN (1.35 m/s vs 1.39 m/s vs 1.54 for F ≥ 2, 1.44 m/s vs 1.58 m/s vs 1.6 m/s for F3, 1.69 m/s, 1.84 m/s, 1.86 m/s for F4). FIB-4 (0.82–0.86) and APRI (0.78–0.82) yielded lower AUC in prediction of significant fibrosis and cirrhosis than ARFI elastography (0.89–0.95). Conclusion: ARFI elastography is a reliable method for non-invasive staging of liver fibrosis in CHC patients when compared to TE with a good diagnostic performance comparable to FIB-4 and APRI scores for the prediction of significant fibrosis and cirrhosis.